Fashion and Authors’ Moral Rights - Härkönen, Heidi (Oxford University Press, 2025)
Due to the judgments Cofemel and Brompton from the Court of Justice of the European Union (CJEU), it is certain that the standard of copyright protection for works of applied art is the same as for any other work categories. However, the harmonising effect of these judgments only extends to the author’s economic rights, and not their moral interests. The moral rights of authors have not been popular topics in legal literature concerning copyright and works of applied art. This raises the question of to what extent moral rights apply to these works, which many national copyright laws used to discriminate against prior to the guidance from the CJEU. This multidisciplinary article delves into the complex relationship between moral rights and works of applied art in the specific context of fashion design. It appears that moral rights are absent from the standard practice in the fashion sector. This is evident, inter alia, in the fact that typically only renowned designers are attributed as authors. The article notes that there is no legally valid reason for fashion houses to overlook designers’ right of attribution. The right of integrity, however, has much less practical significance in the fashion sector. This article suggests the correct approach to moral rights in the fashion sector. The focus is on the European author’s rights tradition. The moral rights tradition of the Nordic states is used as a reference point because it allows for the consideration of the realities in different creative sectors without disrespecting authors’ personal interests.